The Textual Threshold and Its Impact on Textual Cohesion: Qadīsha as a Model - ghilous, salah (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(–header-height)" dir="auto" data-turn-id="89bad2c1-851c-405d-9595-f0e05b42f5cf" data-testid="conversation-turn-135" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:a6b2ebb2-304a-48ab-8736-5ad337282e90-67" data-testid="conversation-turn-136" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="28fdf352-ae38-44f2-9f01-fd29a3e80e4e" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> The novel Qadīsha is a literary work by the author Rabah Zrif, in which he expresses the intangible heritage of the Awlad Draj through narrative and dialogue, depicting the lives of a group of characters who operate within a specific social framework defined by time and place (the Eastern Hedna). The Awlad Draj throne forms the backdrop from which he draws upon his deeply held convictions, transforming them into artistic structures and a remarkable narrative stance. The theme of communication is among the topics that modern linguistic research has given great importance to, aiming to understand its nature, the way it occurs, and the mechanisms it relies on in the process of conveying meaning.